Formation of Logit-Model for Predicting the Probability of Bankruptcy of Ukrainian Enterprises - Ivanov , S.; Sharanov , R.; Vatchenko , O.; Vatchenko , B.; Razumova, H. (Science and Innovation, 2023)
Introduction. Uncertainty and instability in the modern economy have put a large number of businesses of various forms of ownership on the verge of bankruptcy. Given the above, the development of a new methodological approach to predicting (or prognosticating) the probability of bankruptcy becomes particularly relevant. Problem Statement. In modern economic science, there have been many studies in the field of analysis and assessment of the probability of bankruptcy, but most of them have been outdated and not adapted to the Ukrainian economy, which makes it necessary to build and implement at enterprises such a model for prognosticating the probability of bankruptcy, which would be able to detect negative trends that can lead to bankruptcy in the present-day Ukrainian conditions. Purpose. The purpose of this research is to study the evolution of the methodological approaches to predicting the probability of bankruptcy and building a logit model based on the data of Ukrainian enterprises in recent years. Material and Methods. Empirical, experimental, and theoretical methods of research, methods of correlation and regression analysis have been used in this research. Microsoft Excel and IBM SPSS Statistics application packages have been employed to process the selected statistical data of Ukrainian enterprises. Results. The evolution of views and methodological approaches to predicting the probability of bankruptcy of enterprises has been studied. The main advantages and disadvantages of methods and models currently used in prognosticating the probability of bankruptcy have been determined. A sample of Ukrainian enterprises has been formed, indicators affecting bankruptcy have been determined, and as a result, a logit model for prognosticating the probability of bankruptcy has been developed. It is easy to use and has a high predictive quality. Conclusions. The developed logit-model has been proposed for the analysis of enterprise’s financial position in terms of prognosticating crises, insolvency, and bankruptcy.